There Is No Direct Causal Relationship Between Coronary Artery Disease and Alzheimer Disease: A Bidirectional Mendelian Randomization Study - Aifang Zhong; Yejun Tan; Yaqiong Liu; Xiangping Chai; Weijun Peng (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The association between poor cardiovascular health and cognitive decline as well as dementia progression has been inconsistent across studies. This study used Mendelian randomization (MR) to investigate the causal relationship between Alzheimer disease (AD), circulating levels of total‐tau, and coronary artery disease (CAD). Methods and Results This study used MR to investigate the causal relationship between AD or circulating levels of total‐tau and CAD, including ischemic heart disease, myocardial infarction, coronary heart disease, coronary atherosclerosis, and heart failure. The primary analysis used the inverse‐variance weighted method, with pleiotropy and heterogeneity assessed using MR‐Egger regression and the Q statistic. The overall results of the MR analysis indicated that AD did not exhibit a causal effect on heart failure (odds ratio [OR], 0.969 [95% CI, 0.921–1.018]; P=0.209), myocardial infarction (OR, 0.972 [95% CI, 0.915–1.033]; P=0.359), ischemic heart disease (OR, 1.013 [95% CI, 0.949–1.082]; P=0.700), coronary heart disease (OR, 1.005 [95% CI, 0.937–1.078]; P=0.881), or coronary atherosclerosis (OR, 0.987 [95% CI, 0.926–1.052]; P=0.690). No significant causal effect of CAD was observed on AD in the reverse MR analysis. Additionally, our findings revealed that CAD did not influence circulating levels of total‐tau, nor did circulating levels of total‐tau increase the risk of CAD. Sensitivity analysis and assessment of horizontal pleiotropy suggested that these factors did not distort the causal estimates. Conclusions The findings of this study indicate the absence of a direct causal relationship between AD and CAD from a genetic perspective. Therefore, managing the 2 diseases should be more independent and targeted. Concurrently, investigating the mechanism underlying their comorbidity may not yield meaningful insights for advancing treatment strategies.